Missile defence : international, regional and national implications - Heurlin, Bertel; Rynning, Sten, 1967- (Contemporary security studies., 2005)
US missile defence policy plays a crucial part on the international scene and is typically studied from US perspectives. This book is different. It delivers sharp analyses of regional and national variations and integrates them with US viewpoints. This b.